Application of BaY2F8:Er3+,Yb3+ and Mg8Ge2O11F2:Mn4+ in improving the lighting quality of phosphor-in-glass based white light-emitting diodes with the dual-convex design - Huu Phuc Dang; Phung Ton That (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Although the luminous of the remote phosphor structure tends to be better than that of the in-cup or conformal phosphor structures, the poor light quality prevents this lighting method from being widely used. It is recognized through experiments that the two-layer remote phosphorus structure should be used to improve color rendering index (CRI) and color quality ratio (CQS) for WLEDs. In the experiments, WLED structures containing green BaY2F8:Er3+,Yb3+ or red Mg8Ge2O11F2:Mn4+ phosphor on the yellow YAG:Ce3+ phosphor were performed at 8500 K.. After that, Mg8Ge2O11F2:Mn4+ and BaY2F8:Er3+,Yb3+ concentrations in each WLED structure is adjusted until chromatic performance reached the finest quality. As a result, Mg8Ge2O11F2:Mn4+is proved to bring great benefits to the increase of CRI and CQS. Specifically, the greater the concentration of Mg8Ge2O11F2:Mn4+, the better CRI and CQS because of the additional red-light material from this phosphor. The other phosphor material, green BaY2F8:Er3+,Yb3+ phosphor, is beneficial for the expansion of luminous flux. However, if the concentration of Mg8Ge2O11F2:Mn4+ or BaY2F8:Er3+,Yb3+ is over the limit, the decrease in lumen output and chromatic quality will occur. While doing the experiment, Mie-scattering theory and the Beer’s law are great tools to verify the accuracy of results. The results of this article can serve the purpose of improving WLEDs fabrication to produce higher quality product.